Peranan Evaluasi Sistem Pengendalian Internal Piutang Usaha Dalam Upaya Meningkatkan Efektivitas Organisasi - Abdillah Firdaus; Arif Afriady (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
PDAM Solok Regency faces problems in internal control of its business receivables, such as bad debt problems, the length of the billing period, and the occurrence of cash lapping cases that make researchers interested in conducting research. This study aims to provide an evaluation of the internal control system for accounts receivable using a control matrix based on of COSO’s internal control integrated framework at PDAM Kabupaten Solok. This study uses a qualitative descriptive method with the type of data in the form of subject data and documentary data and data sources in the form of primary data and secondary data. Data collection techniques are interviews, observation, and documentation. The results of this research indicates that there is still an internal control system that has been implemented and has not been implemented by PDAM Solok Regency on accounts receivable, but overall it is quite effective and efficient.